Social representations informing discourses of young leaders: a case study of Tanzania - Salles-Haussler, Valeria Cristina (Department of Social Development, 2023)
This dissertation is a theoretical and textual analysis of the discursive practice of young leaders in Tanzania, as a means to understand the dominant representations of a group that plans to take over the leadership of the country In the future. Representations are collective discursive formations conditioned by historical possibilities and cultural context. The exploratofy approach adopts Constructivism as a major philosophical paradigm for social realities and presents a case study of twenty-five participants who are young political leaders operating in Tanzania and trainees on the Youth Leadership Training Programme (YLTP), run by the Friedrich Ebert Foundation, a German not-for-profit organization guided by democratic values. All of the participants had 'leadership' positions In their own orginizations. In 2003, they were interviewed and wrote essays on different topics related to leadership in Tanzania, while I was living in that country and working as short-term trainer for the YLTP. As a member of the team of trainers of the first YLTP, I was invited to lead its end-of.programme evaluation, the results of which left open questions regarding the relationship between Tanzanian history and cultural contexts, and the choice of curriculum and method of the YLTP. This research intends, in its analysis of the issues raised by these questions, to contribute to the future design of leadership-training programmes in Tanzania. There are two parts: part I, 'the researcher, the object and the method' gives an account of my philosophical trajectory, formulates the epistemological foundations upon which the analysis is built, and proposes a methodological tool that has not been used in the English-speaking world yet: the discourse of the collective subject (DCS). Conventional explanations ignore the power of discourse and its role in construction, maintenance and resistance to ideologies. The choice of discourse analysis aims at unveiling the Tanzanian culture-specific ideological constructions and the powers that, in interaction, frame and mediate discourses and meaning-making. Part II searches for those 'relationships between history, social representations and contemporary discourses of young leaders', showing how the ideological forces operating in Tanzania determine rules of formation for the young leaders' discourses. Three types of dominant discourses are articulated among the young leaders. One, which I named humanistic discourse, is framed by constructions of socialism and Ujamaa, brotherhood, egalitarianism and Pan-Africanism. This dominant discursive practice is, however, interspersed with liberal discourses, which frame the world within streams of the modernization paradigm, reconstructing meanings in Tanzania. Both discursive practices are found to be mediated by a patriarchal discourse, which weaves through old and new representations of the young leaders in that country. The analysis of the discourses and the conclusions regarding social representations helped develop some recommendations in the form of insights for future leadership-training programmes In Tanzania. Those recommendations aim particularly at linking the domain of the 'personal' to the domain of the 'political', both found to pertain to different, and sometimes conflicting, genres and narratives among the young leaders.